2011
DOI: 10.1089/neu.2010.1646
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Window Analysis of the Neuroprotective Effects of Cyclosporine A after Traumatic Brain Injury

Abstract: Mitochondrial dysfunction plays a pivotal role in secondary cell death mechanisms following traumatic brain injury (TBI). Several reports have demonstrated that inhibition of the mitochondrial permeability transition pore with the immunosuppressant drug cyclosporine A (CsA) is efficacious. Accordingly, CsA is being moved forward into late-stage clinical trials for the treatment of moderate and severe TBI. However, several unknowns exist concerning the optimal therapeutic window for administering CsA at the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 67 publications
1
64
1
Order By: Relevance
“…Based on our observations and evidence from experimental models, we propose that the mitochondrial structural alterations that occur in human cortical TBI tissue are associated with both perturbations in mitochondrial dynamics and with osmotic swelling associated with mitochondrial permeability transition (MPT) pore openings. 2,[57][58][59][60] It has now been demonstrated that inhibition of the MPT after TBI is a viable neuroprotective approach [61][62][63] and can improve the favorable outcomes of severe TBI patients. 64,65 The several interrelated mitochondrial dynamic processes, such as fusion, fission, anterograde and retrograde transport in axons, turnover, and interaction with cytoskeleton and other organelles, form a complex interacting network that governs mitochondrial function and thereby cellular integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our observations and evidence from experimental models, we propose that the mitochondrial structural alterations that occur in human cortical TBI tissue are associated with both perturbations in mitochondrial dynamics and with osmotic swelling associated with mitochondrial permeability transition (MPT) pore openings. 2,[57][58][59][60] It has now been demonstrated that inhibition of the MPT after TBI is a viable neuroprotective approach [61][62][63] and can improve the favorable outcomes of severe TBI patients. 64,65 The several interrelated mitochondrial dynamic processes, such as fusion, fission, anterograde and retrograde transport in axons, turnover, and interaction with cytoskeleton and other organelles, form a complex interacting network that governs mitochondrial function and thereby cellular integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly the lower dose (2.5 mg/kg) was more effective than the higher dose (5 mg/kg). CsA has been shown to have an early therapeutic window and to inhibit a myriad of molecular processes and histological outcomes including reduced brain tissue BDP generation and decreased lesion volume [50][51][52] . To our knowledge, this is the first study to indicate that acute serum GFAP correlated to BDPs as well as neurobehavioral metrics.…”
Section: Brain Tissue Break-down Products Indicate Persistent Proteolmentioning
confidence: 99%
“…The half-lives of melatonin and DEX are 27 and 200 min respectively (Cevc & Blume 2004, Venegas et al 2012. Several recent results have illustrated the importance of initiating therapeutic interventions as soon as possible following TBI, preferably within 4 h post-injury, to achieve the best possible neuroprotective effect (Sullivan et al 2011). …”
Section: Experimental Groupsmentioning
confidence: 99%